Residue radiocarbon AMS dating review and preliminary sampling protocol suggestions. (September 2015) - Yates, A.B.; Smith, A.M.; Bertuch, F.
Abstract: Radiocarbon dating of microgram residues is a relatively new field in archaeological research and is currently limited by a lack of analytical protocols and instrumentation. Successful applications of Accelerator Mass Spectrometry (AMS) have demonstrated the potential of the technique on small samples but also revealed challenges and problems, especially with contamination. This paper reviews the literature on AMS radiocarbon dated residues using microgram sized carbon samples. Samples from archaeological studies are targeted, including residues from lithics, ceramics and rock art. We examine data helpful to avoiding contamination and to facilitating residue radiocarbon dating. As a result we present a preliminary sampling protocol to assist archaeologists in preventing contaminant transfer from fieldwork onwards. Highlights: Residue radiocarbon dating reviewed on archaeological substrates: lithic artefacts, ceramics and rock art. Focus on contaminant prevention. Contaminant sources during fieldwork, storage, artefact examination in laboratory identified. Sampling protocol developed.